CARACTERES MORFOLÓGICOS DOS DIÁSPOROS, ANÁLISE DE GRUPOS ECOLÓGICOS E SÍNDROMES DE DISPERSÃO DE PLANTAS AQUÁTICAS - VITORIA SILVA FABIANO (2021)
Aquatic plants are highly adapted to aquatic environments and are essential for their maintenance, as they participate in several ecological interaction networks. The strong relationship with water is evidenced by morphoanatomical structures that reflect the degree of adaptation to the aquatic environment, also observed in morphofunctional traits present in diaspores. The morphology of aquatic plant diaspores can provide important information related to the selection of characteristics and composition of communities, dispersal strategies, seed banks and species recruitment, assisting in taxonomy and phylogeny and providing essential data for restoration and wetland management. The present work provides a detailed description of the morphology of the diaspores and evaluates the convergence of characters within the groups of life forms and dispersion syndromes, as well as investigating attributes related to morphological characters. For this, 16 morphological traces of 37 fruits and 47 seeds were taken. For the description of the diaspores, electron micrographs made with Scanning Electron Microscopy were used. The work included 84 species, belonging to 32 botanical families, covering amphibious, emergent, epiphytic, fixed and free floating and fixed and free submerged life forms. The plants sampled derived as the main dispersion related to hydrochory, autochory, anemochory and zoochory, which may occur from two or three types of syndromes. Our analyzes demonstrated that there is no convergence of characteristics within the life forms and dispersal syndromes, despite this, there is a demand for the dispersion strategy on the morphology of the diaspores. Furthermore, there seems to be a phylogenetic factor influencing the selection of morphological traits in fruits, which we did not observe in seeds. The association of dispersal strategies seems to be related to the production of this ecological process in the selection of life-history traits, with characters highly adapted to dispersal vectors being observed.